Performance of a high-throughput next-generation sequencing method for analysis of HIV drug resistance and viral load. (8th August 2020) - Fogel, Jessica M; Bonsall, David; Cummings, Vanessa; Bowden, Rory; Golubchik, Tanya; de Cesare, Mariateresa; Wilson, Ethan A; Gamble, Theresa; del Rio, Carlos; Batey, D Scott; Mayer, Kenneth H; Farley, Jason E; et al.
Abstract: Objectives: To evaluate the performance of a high-throughput research assay for HIV drug resistance testing based on whole genome next-generation sequencing (NGS) that also quantifies HIV viral load. Methods: Plasma samples ( n  =   145) were obtained from HIV-positive MSM (HPTN 078). Samples were analysed using clinical assays (the ViroSeq HIV-1 Genotyping System and the Abbott RealTime HIV-1 Viral Load assay) and a research assay based on whole-genome NGS (veSEQ-HIV). Results: HIV protease and reverse transcriptase sequences ( n  =   142) and integrase sequences ( n  =   138) were obtained using ViroSeq. Sequences from all three regions were obtained for 100 (70.4%) of the 142 samples using veSEQ-HIV; results were obtained more frequently for samples with higher viral loads (93.5% for 93 samples with >5000 copies/mL; 50.0% for 26 samples with 1000–5000 copies/mL; 0% for 23 samples with <1000 copies/mL). For samples with results from both methods, drug resistance mutations (DRMs) were detected in 33 samples using ViroSeq and 42 samples using veSEQ-HIV (detection threshold: 5.0%). Overall, 146 major DRMs were detected; 107 were detected by both methods, 37 were detected by veSEQ-HIV only (frequency range: 5.0%–30.6%) and two were detected by ViroSeq only. HIV viral loads estimated by veSEQ-HIV strongly correlated with results from the Abbott RealTime Viral Load assay ( R 2  = 0.85; n  =   142). Conclusions: The NGS-based veSEQ-HIV method provided results for most samples with higher viral loads, was accurate for detecting major DRMs, and detected mutations at lower levels compared with a method based on population sequencing. The veSEQ-HIV method also provided HIV viral load data.